A critical analysis of the production and reproduction efficiency of Nguni cattle (Bos indicus africanus) in different geographical regions of South Africa - Webb, E.C. (Edward Cottington) (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2019.